EVALUATION OF ENVIRONMENTAL SITUATION IN ACCIDENTS WITH HAZARDOUS AND TOXIC CARGO - Plakhotnik, V. M.; Yaryshkina, L. O.; Boichenko, A. M. (Science and Transport Progress, 2003)
General directions for emergency procedure and organization measures, aimed at eliminating the after-effects of railway accidents with dangerous and toxic freights, are determined, in view of assessing the ecological consequences of such accidents.